A=(+2.2)-(+3.3)+(-4.4)-(-5.5)

B=(-3.25)+(-2.75)-(4.25)+(-2.5)

C=(-10.4)-(+9.3)-(-27)-(+6.1)

A=(-8)+(+6)+(+8)+(-7)+(-2)

B=(+'4)-(+5)+(-6)+(+5)-(-8)

C=(-7)+(-1.5)-(+7)+(+1.5)+(-6)

D=(-1.25)+(-2.75)-(-1.25)-(+0.25)

1

Réponses

2014-02-17T17:33:20+01:00
A=(+2.2)-(+3.3)+(-4.4)-(-5.5)
A = 2,2 - 3,3 - 4,4 + 5,5
A = -1,1 + 1,1
A = 0

B=(-3.25)+(-2.75)-(4.25)+(-2.5)
B = -3,25 - 2,75 - 4,25 - 2,5
B = -6 -4,25 - 2,5
B = -10,25 - 2,5
B = -12,75

C=(-10.4)-(+9.3)-(-27)-(+6.1)   
C = -10,4 - 9,3 + 27 - 6,1
C = - 19,7 + 27 - 6,1
C = 7,3 - 6,1
C = 1,2

A=(-8)+(+6)+(+8)+(-7)+(-2)
A = - 8 + 6 + 8 - 7 - 2
A = -2 + 8 - 7 - 2
A = 6 - 7 - 2
A = -1 - 2
A = -3

B=(+4)-(+5)+(-6)+(+5)-(-8)
B = 4 - 5 - 6 + 5 + 8
B = -1 - 6 + 5 + 8
B = -7 + 5 + 8
B = -2 + 8
B = 6

C=(-7)+(-1.5)-(+7)+(+1.5)+(-6)
C = -7 - 1,5 - 7 +1,5 - 6
C = -8,5 - 7 + 1,5 - 6
C = -15,5 + 1,5 - 6
C = -14 - 6
C = -20

D=(-1.25)+(-2.75)-(-1.25)-(+0.25)

D = -1,25 - 2,75 +  1,25 - 0,25
D = -4 + 1,25 - 0,25
D = -2,75 - 0,25
D = -3